THE EFFECT OF SALINITY ON THE PHYSIOLOGICAL PERFORMANCE OF ASIAN REDTAIL CATFISH SEEDS (Hemibagrus nemurus) - Putra, Mutlas Ade; Tang, Usman M; Syawal, Henni (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2023)
This research was conducted 30 days from June to July 2022 at the Aquaculture Laboratory, Faculty of Fisheries and Marine Sciences, Universitas Riau, Pekanbaru. This study aimed to analyze the osmoregulation response of the Asian redtail catfish to different salinities and to obtain optimal salinity for good physiological performance for the Asian redtail catfish. The method used was an experimental method using a completely randomized design (CRD) with five treatments and four replications, namely, three ppt salinity treatment, six ppt salinity treatment, nine ppt salinity treatment, 12 ppt salinity treatment, and 15 ppt salinity treatment. The test fish used were Asian redtail catfish with an average size of 7.17±0.04 cm. Asian redtail catfish seeds were obtained from the Tibun Fish Seed Center, Kampar. The container used is an aquarium with a size of 60x40x40 cm. Research data shows that nine ppt salinity is the best for Asian redtail catfish osmoregulation of 0.5 mOsm/L H2O. The best cortisol hormone content is found at three ppt salinity, the lowest oxygen consumption is at three ppt salinity of 0.9 mgO2/g/hour, the best survival was found at three ppt salinity of 100%, and the growth in weight and length was in the three ppt treatment of 8.90 g and 2.04 cm. Water quality parameters include temperature 25-30oC and dissolved oxygen 5.04-8.04 ppm.